The Preliminary Development and Validation of a Trauma‐Related Safety‐Seeking Behavior Measure for Youth: The Child Safety Behavior Scale (CSBS). Issue 5 (19th October 2018) - Alberici, Alice; Meiser‐Stedman, Richard; Claxton, Jade; Smith, Patrick; Ehlers, Anke; Dixon, Clare; Mckinnon, Anna
Abstract: Safety‐seeking behaviors (SSBs) may be employed after exposure to a traumatic event in an effort to prevent a feared outcome. Cognitive models of posttraumatic stress disorder propose SSBs contribute to maintaining this disorder by preventing disconfirmation of maladaptive beliefs and preserving a sense of current threat. Recent research has found that SSBs impact children's posttraumatic stress symptoms (PTSS) and recovery. In this paper, we sought to develop and validate a novel 22‐item Child Safety Behavior Scale (CSBS) in a school‐based sample of 391 pupils (age 12–15 years) who completed a battery of questionnaires as well as 68 youths (age 8–17 years) who were recently exposed to a trauma. Of the sample, 93.1% ( N = 426) completed the new questionnaire. The sample was split ( n = 213), and we utilized principal components analysis alongside parallel analysis, which revealed that 13 items loaded well onto a two‐factor structure. This structure was superior to a one‐factor model and overall demonstrated a moderately good model of fit across indices, based upon a confirmatory factory analysis with the other half of the sample. The CSBS showed excellent internal consistency, r = .90; good test–retest reliability, r = .64; and good discriminant validity and specificity. In a multiple linear regression, SSBs, negative appraisals, and number of trauma types each accounted for unique variance in a model of PTSS. This study provides initial support for the use of the CSBS in trauma‐exposed youth as a valuable tool for further research, clinical assessment, and targeted intervention. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) El Desarrollo Preliminar y la Validación de una Medida Conductual de Búsqueda de Seguridad Relacionada al Trauma para Jóvenes: La Escala de Comportamiento de Seguridad Infantil (CSBS, en sigla en inglés) DESARROLLO DE LA ESCALA DE COMPORTAMIENTO DE SEGURIDAD INFANTIL Los comportamientos de búsqueda de seguridad (SSBs, en su sigla en inglés) pueden ser empleados después de la exposición a un evento traumático en un esfuerzo por evitar un resultado temido. Los modelos cognitivos del trastorno de estrés postraumático proponen que los SSBs contribuyen a mantener este trastorno al evitar la refutación de las creencias desadaptativas y preservar un sentido de amenaza actual. Las investigaciones recientes han encontrado que los SSBs tienen un impacto en los síntomas de estrés postraumático (SEPT) y en la recuperación de los niños. En este documento, buscamos desarrollar y validar una nueva Escala de Conducta de Seguridad Infantil (CSBS) de 22 ítems en una muestra escolar de 391 estudiantes (de 12 a 15 años) que completaron una batería de cuestionarios y de 68 jóvenes (de 8 a 17 años) que estuvieron expuestos recientemente a un trauma. De la muestra, el 93.1% ( N = 426) completó el nuevo cuestionario. La muestra se dividió ( n = 213) y utilizamos el análisis de componentes principales junto con el análisis paralelo, revelando que 13 ítems cargaron adecuadamente en una estructura de dos factores. Esta estructura fue superior a un modelo de un factor y, en general, fue un modelo de ajuste moderadamente bueno entre los índices que investigamos (utilizando el análisis factorial confirmatorio con la otra mitad de la muestra). La CSBS mostró una excelente consistencia interna, r = .90; buena confiabilidad test‐retest, r = .64; y buena validez discriminante y especificidad. En una regresión lineal múltiple, los SSBs, las evaluaciones negativas, y el número de tipos de traumas explicaron cada uno una parte de la varianza en un modelo de SEPT. Este estudio proporciona apoyo inicial para el uso de la CSBS en jóvenes expuestos al trauma como una herramienta clínicamente valiosa para futuras investigaciones, evaluaciones clínicas, e intervenciones específicas. 抽象: Traditional and Simplified Chinese Abstracts by the Asian Society for Traumatic Stress Studies (AsianSTSS) 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 The Preliminary Development and Validation of a traumarelated safety‐seeking‐seeking behaviour measure for youth: the Child Safety Behaviour Scale (CSBS) Traditional Chinese 標題: 為青少年而設的創傷相關安全感行為測量的初步設計和驗證:兒童安全感行為量表(CSBS) 撮要: 人在經歷創傷事件後, 為提防害怕的事件發生, 可能會採取尋找安全感的行為(SSBs)。創傷後壓力症的認知模型提出, SSBs會預防適應不良的信念被推翻並保持當前的威脅感, 致使病患維持。而近期研究發現, SSBs對兒童的創傷後壓力症狀(PTSS)和康復有所影響。本研究旨在設計和驗證一個新的22項兒童安全感行為量表(CSBS)。樣本屬學校為本, 有391名學生(年齡為12–15歲)完成了一系列問卷, 並有68 名青少年 (年齡為8–17歲)近期經歷了一次創傷。樣本中93.1% (N = 426)完成了新問卷。我們把樣本分開兩半(n = 213), 利用主成分分析法及平行分析法, 發現13個項目能適切地融於一個二因素模型, 它比單因素模型更好, 綜觀所有我們檢視的指數來說 (對另一半樣本進行驗證性因素分析), 整體上是適切度為中度良好的模型。CSBS的內部一致性為極佳(r = .90);重測信度為良好 (r = .64), 判別效度和特殊性亦為良好。多元線性迴歸分析顯示, 在一個PTSS模型裡, SSBs、負向評價和創傷類別數量都分別構成獨特的方差。本研究提供了初步數據, 支持對受創青少年使用CSBS, 證明它對未來研究、臨床評估和針對性干預治療都是有用工具。 Simplified Chinese 标题: 为青少年而设的创伤相关安全感行为测量的初步设计和验证:儿童安全感行为量表(CSBS) 撮要: 人在经历创伤事件后, 为提防害怕的事件发生, 可能会采取寻找安全感的行为(SSBs)。创伤后压力症的认知模型提出, SSBs会预防适应不良的信念被推翻并保持当前的威胁感, 致使病患维持。而近期研究发现, SSBs对儿童的创伤后压力症状(PTSS)和康复有所影响。本研究旨在设计和验证一个新的22项儿童安全感行为量表(CSBS)。样本属学校为本, 有391名学生(年龄为12–15岁)完成了一系列问卷, 并有68 名青少年 (年龄为8–17岁)近期经历了一次创伤。样本中93.1% (N = 426)完成了新问卷。我们把样本分开两半(n = 213), 利用主成分分析法及平行分析法, 发现13个项目能适切地融于一个二因素模型, 它比单因素模型更好, 综观所有我们检视的指数来说 (对另一半样本进行验证性因素分析), 整体上是适切度为中度良好的模型。CSBS的内部一致性为极佳(r = .90);重测信度为良好 (r = .64), 判别效度和特殊性亦为良好。多元线性回归分析显示, 在一个PTSS模型里, SSBs、负向评价和创伤类别数量都分别构成独特的方差。本研究提供了初步数据, 支持对受创青少年使用CSBS, 证明它对未来研究、临床评估和针对性干预治疗都是有用工具。